PENANGANAN KELUHAN MASYARAKAT PENGGUNA JASA HOTEL ON INN GUESTHOUSE DI WONASA TENGA KARAME MANADO - SAWAL, VIRGINIA AMELIA; RURU, JOORIE MARHAEN; PLANGITEN, NOVVA (Sam Ratulangi University, 2018)
AbstrackHandling Public complaints in need, because every complaint that is given very regure from certainsparties. Similarly in the hotel on in as a place to rest the hotel must be able to deal with any complaints andshould be able to handle it rather bay way of giving ecordingly capable of real action.The handling ofcomplaints from the users of hotel on in service has been running quite well. Although there are fewconstraints coming from the users but the hotel on in has been able to show the quality to give value morethan the community therefore. This study will answer the question, how the procedure of handling the userscommunity complaints service hotel on in guesthouse in Wonasa Tenga Karame Manado? In this researchis limited by some elements Grievance handling according to Garton (2005) that it. Commitment,Accessibility Responsive, Transparency and Responsible. The research user descriptive skin methodthrough interview of 10 informants and tracing of additorial documents in the from of a list of interviewguides recording and writing tools. The results of this study indicate that the handling of complaints publicservice hotel on in users are running pretty well.